2014
DOI: 10.1111/acem.12444
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Characteristics of a Clinical Screening Tool in Combination With Measuring Bedside Lactate Level in Emergency Department Patients With Suspected Sepsis

Abstract: Background: Early identification of sepsis and initiation of aggressive treatment saves lives. However, the diagnosis of sepsis may be delayed in patients without overt deterioration. Clinical screening tools and lactate levels may help identify sepsis patients at risk for adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 18 publications
(26 reference statements)
4
51
0
1
Order By: Relevance
“…Keywords related to symptom presentation are not included in the existing screening tools for sepsis identification within emergency care [17, 18], which should be reconsidered. However, before this is done, prospective studies evaluating the sensitivity and specificity of these keywords needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords related to symptom presentation are not included in the existing screening tools for sepsis identification within emergency care [17, 18], which should be reconsidered. However, before this is done, prospective studies evaluating the sensitivity and specificity of these keywords needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The inadequate sensitivity and specificity of the SIRS criteria has been a contributing factor to a recently suggested revision of the sepsis definition [1]. Nevertheless, existing sepsis screening tools are still based mainly on SIRS criteria [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…[16] The use of lactic acid assays in the ED and procalcitonin and c-reactive protein assays in the intensive care unit have been studied as screening modalities to aid in sepsis recognition. [22-24] Management strategies in the ED have focused on time-based bundles created to help direct resuscitation, while inpatient sepsis management strategies have focused on appropriate antibiotic stewardships, lung-protective ventilation strategies and the use of hospital rapid response teams. [9, 16, 25]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (17,18) found that about one-third to one-half of patients with vasopressor-dependent septic shock did not express lactate on presentation and that lactate remained below 2.0 mmoL L À1 . More recently, Singer et al (19) demonstrated that a lactate level of !2 mmoL L À1 is associated with an increased need for vasopressors (odds ratio [OR] 1.54, 95% CI 1.13-2.12).…”
Section: Discussionmentioning
confidence: 99%